Implementation analysis and problems of implementing of literacy movement in primary schools - Amelia, Delora Jantung; Wahyu Putri Utami, Ima; Ulum , Bahrul (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this study is to analyze the application and problems of implementing literacy movement in primary schools. This type of research is descriptive qualitative. The data sources in this study were all school residents at SDN Tlogomas 2 Malang City. The research data was conducted using interview techniques and documentation using interview instruments and guidelines. The implementation of literacy movement at SDN Tlogomas 2 Malang City is divided into three stages: habituation, development, and learning. The literacy movement also had some problems that trying to overcome together at SDN Tlogomas 2.